1991
DOI: 10.3349/ymj.1991.32.4.370
|View full text |Cite
|
Sign up to set email alerts
|

Cystic meningiomas in infancy

Abstract: A suprasellar meningioma with multiple intratumoral cysts in a 6-month-old boy is reported. A review of literature disclosed only 11 cases so far. They showed a characteristic predominance in males and predominance of fibroblastic type on pathological examination. Intratumoral cystes are less common than peritumoral cysts. The various hypothesis regarding cyst formation are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Sridhar [21] noted that all peritumoural cysts were in males. Sharama [20] in a review of 11 cases found that intratumoural cysts were less common than peritumoural cysts; and that they were more common in males. In the present series (Table 2) intratumoural cysts were found in 5 cases including 2 males.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Sridhar [21] noted that all peritumoural cysts were in males. Sharama [20] in a review of 11 cases found that intratumoural cysts were less common than peritumoural cysts; and that they were more common in males. In the present series (Table 2) intratumoural cysts were found in 5 cases including 2 males.…”
Section: Discussionmentioning
confidence: 99%
“…In the present series it was 815 observed that massive peritumoural oedema was associated with intratumoural cysts; while oedema was minimal in extratumoural cysts (Table 2). Cyst formation is more common in children [2,15,20,21]. Congenital meningiomas may produce fluid [2].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the literature we were able to find out only 15 cases of cystic meningiomas under 12 months of age, including our own case: among these, nine were fibroblastic meningiomas, two were malignant and the only atypical meningioma was the present case (Table 1; 6–19). Besides, all but our patient were male, and the follow‐up, ranging from 10 days to 4 years, reports only one death.…”
Section: Discussionmentioning
confidence: 80%